Ensino de arte no universo autista: um relato de extensão da faculdade de artes do Paraná - Fernandes, Lorena Barolo (2010)
The syndrome of the Autistic Spectrum Disorders (ASD) is still considered a great challenge for scholars. Indeed, science has not confirmed it yet. All scientists know, thus, is that the main characteristic of this syndrome is strongly linked to those three human domains: communication, sociability, and imagination. In fact, the individual with ASD shows this disturb in his/her behavior due to his/her isolation from other people and also from the environment. Thus, the aim of this study was to investigate sensorial experiences by the use of some artistic activities that might enrich students with ASD. This research is the outcome of a previous Visual Art Workshop Project led by Faculdade de Artes do Paraná – FAP and Escola de Educação Especial Alternativa. Such a Project worked with eight students who carried a severe level of ASD. This investigation started with an ASD short background; also, it analyzed the major difficulties experienced by the special education at schools as well as it studied the main documents which lead some inclusion policies. The following chapter focused either the Art Teaching for the autistic or Walter Benjamin’s thoughts on the relationship between Education and Art. In the following chapter, this paper managed to depict the thorough methodology used towards that workshop: a deep study of the ASD students’ field, profile, and anemnesis was performed. It also showed the outcome of that workshop together with some pedagogic recommendations for the ASD carrier. In the end, questions developed during the course of this investigation were reinforced and emphasized. In short, this paper pointed out that, during this Visual Arts workshops, one can easily stress that, not only is the artistic experiences a major aid to ASD students but also it is a strong link among those students, the environment, and Art.